The Pudding Problem - Berger, Joe (London McELDERRY Books, 2017)
"A boy must untangle the web of lies he has created in order to prove his innocence when strange things start happening"-- Provided by publisher
Including illustrations
Keywords: Truthfulness and falsehood -- Humorous stories -- Children's stories